2014
DOI: 10.3945/jn.114.191007
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea, Black Tea, and Oolong Tea Polyphenols Reduce Visceral Fat and Inflammation in Mice Fed High-Fat, High-Sucrose Obesogenic Diets

Abstract: Green tea (GT) and caffeine in combination were shown to increase energy expenditure and fat oxidation, but less is known about the effects of black tea (BT) and oolong tea (OT). This study investigated whether decaffeinated polyphenol extracts from GT, BT, and OT decrease body fat and inflammation in male C57BL/6J mice fed high-fat/high-sucrose [HF/HS (32% energy from fat, 25% energy from sucrose)] diets. Mice were fed either an HF/HS diet with 0.25% of polyphenol from GT, OT, or BT or a low-fat/high-sucrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 49 publications
6
64
0
2
Order By: Relevance
“…Consistent with these findings, Heber et al (2014) reported that C57BL/6J mice gained less weight on an HF/HS diet and supplementation with phenolic-enriched extracts. In the same order, the body composition of mice confirms that the administration of CGT promotes a reduction in body fat accumulation despite the negative effects of the HF/HS diet.…”
Section: Discussionsupporting
confidence: 56%
“…Consistent with these findings, Heber et al (2014) reported that C57BL/6J mice gained less weight on an HF/HS diet and supplementation with phenolic-enriched extracts. In the same order, the body composition of mice confirms that the administration of CGT promotes a reduction in body fat accumulation despite the negative effects of the HF/HS diet.…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, high-fat foods (e.g. sausage, cookies, biscuits, cake, pastries) [33], high-energy (e.g. sugar-sweetened) drinks [34,35], and processed meat [36,37] have been associated with pro-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…The caffeine in white tea may, in part, be responsible for this result, as it is thermogenic and stimulates the oxidation of fat (for review, see Harpaz et al ., ). However, caffeine is unlikely to be solely responsible for this finding, as catechins containing caffeine have a greater thermogenic effect than caffeine alone (Heber et al ., ; Yoneshiro et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were found by Heber et al . (); in their study, Vegf gene expression increased in adipose tissue in mice fed green tea polyphenols. It is possible that the effects of catechins vary in pathological and physiological vascularisation and among different organs.…”
Section: Discussionmentioning
confidence: 97%